Implementing Large-Group Consultation in Comprehensive School Counseling Programs. Issue 4 (2nd October 2021) - Saunders, Rachel; Merlin-Knoblich, Clare
ABSTRACT: Large-group consultation (LGC) is a tool in which professional school counselors deliver key expertise to faculty and staff in their schools while using their group work skills to facilitate meaningful learning. As part of a comprehensive school counseling program, LGC is an efficient, systemic strategy for school counselors to impact students' academic, career, and social/emotional success. In this article, we present best practices when designing and implementing LGC. We also highlight two school counseling case studies to demonstrate the usefulness of LGC.